The Matter of Race: Brotherhood of St. Moses the Black and the Retelling of African American History through Orthodox Christian Forms - Kravchenko, Elena V. (Journal of the American Academy of Religion, 2021)
This article looks at how contemporary African American converts to Orthodox Christianity, specifically the members of the Brotherhood of St. Moses the Black,1 use religion to understand and remember the struggle of Black people against racial discrimination in the United States. As I examine how practitioners interpreted and preserved African American history—the attempts to abolish slavery, the fight to end lynching, and the Civil Rights movement—through Orthodox forms of materiality, I demonstrate that African Americans drew on an established tradition to authorize new ways of practicing Orthodoxy and being Orthodox. I argue that by using icons of the Theotokos to tell stories about her intervention during a lynching, memorializing lives of Black American martyrs in cemetery stones, and engaging with relics of African American saints, these practitioners followed in the footsteps of other Orthodox people—who creatively adopted the ritual life of the Church to their own needs while making an effort to adhere to its traditional dogmatism—and therefore should be considered as a paradigmatic and not an exceptional example of Orthodox Christians.